Associations between heat exposure, vigilance, and balance performance in summer tree fruit harvesters. (February 2018) - Spector, June T.; Krenz, Jennifer; Calkins, Miriam; Ryan, Dawn; Carmona, Jose; Pan, Mengjie; Zemke, Anna; Sampson, Paul D.
Abstract: Background: We sought to evaluate potential mediators of the relationship between heat exposure and traumatic injuries in outdoor agricultural workers. Methods: Linear mixed models were used to estimate associations between maximum work-shift Wet Bulb Globe Temperature (WBGTmax ) and post-shift vigilance (reaction time) and postural sway (total path length) in a cross-sectional sample of 46 Washington State tree fruit harvesters in August–September 2015. Results: The mean (SD) WBGTmax was 27.4 (3.2)°C in August and 21.2 (2.0)°C in September. The mean pre-work-shift participant urine specific gravity indicated minimal dehydration. Twenty-four percent of participants exhibited possible excessive sleepiness. There was no association between WBGTmax and post-shift reaction time or total path length. Conclusions: Heat exposure was not associated with impaired vigilance or balance in this study, in which the overall mean (SD) WBGTmax was 25.9 (4.2)°C. However, the study identified opportunities to ensure adequate pre-work-shift hydration and to optimize sleep and work-shift timing in order to reduce occupational injury and heat-related illness risk. Highlights: Heat exposure was not associated with impaired vigilance or balance in this study. Opportunities to optimize hydration, sleep, and work-shift timing were identified. Addressing these factors may help reduce occupational injury and heat illness risk.